Investigation of pigments in Thai purple rice using electron paramagnetic resonance imaging and HPLC - Kouichi Nakagawa (2020)
© 2019, Center for Academic Publications Japan. All rights reserved. Paramagnetic species (radicals) related pigments in Thai purple rice were investigated by electron paramagnetic resonance (EPR), X-band (9 GHz) EPR imaging (EPRI), and HPLC. The location and distribution of the paramagnetic species in purple and white rice were determined by EPR and EPRI. EPR primarily detected three paramagnetic species in purple rice, which were identified as organic radicals, Mn2+, and Fe3+based on the g-values and hyperfine components of the EPR signals. Noninvasive two-dimensional (2D) EPRI revealed that these stable radicals are primarily located in the pigmented region of purple rice, while very few radicals were observed in the interior of the rice. HPLC revealed that the major compounds were cyanidin-3-O-glucoside and peonidin-3-O-glucoside. EPR, EPR imaging, and HPLC results indicate that the stable radicals contain the radical state of anthocyanins and are mostly found within the pigmented embryo region of purple rice. They could be either associated with antioxidant activities or could be one of the products of their oxidative decomposition.